Selected Lectures of the 18th International Workshop on Neonatology and Pediatrics; Cagliari (Italy); October 19-22, 2022 - - (Hygeia Press di Corridori Marinella, 2022)
Selected Lectures of the 18th International Workshop on Neonatology and Pediatrics • From womb to adulthood • Cagliari (Italy) • October 19th-22nd, 2022    The Workshop has been organized with the patronage of UENPS (Union of European Neonatal and Perinatal Societies), UMEMPS (Union of Middle-Eastern and Mediterranean Pediatric Societies), SIP (Italian Society of Pediatrics), SIN (Italian Society of Neonatology), SIAIP (Italian Society of Pediatric Allergology and Immunology), SI-DOHaD (Italian Society of DOHaD [Developmental Origins of Health and Disease]), SIBioC (Italian Society of Clinical Biochemistry), S.I.P.Ped. (Italian Society of Pediatric Psychology), IAPS (Italian Arabian Society of Pediatrics), IRPS (Italian Romanian Pediatric Society), RSP (Romanian Society of Pediatrics).    LECT 1. PLASTIC IN PLACENTA: WHAT IS IT? WHAT TO DO? • A. Ragusa (Rome, Italy) LECT 2. THE "PLACENTAL PARADOX": A PERPLEXING PHENOMENON IN THE FIELD OF PERINATAL PATHOLOGY. HOW TO SOLVE IT? • C. Gerosa, M. Vincis, G. Faa (Cagliari, Italy) LECT 3. PREVENTION IN PERINATOLOGY OF ALLERGIC DISEASE LATER IN LIFE • D.G. Peroni, B. Polito (Pisa, Italy) LECT 4. NUTRITION AND FOOD MODELS FOR GROWTH AND DEVELOPMENT IN INFANCY AND CHILDHOOD • F. Tandoi, A. Bossi, L. Morlacchi, I. Bresesti, M. Agosti (Varese, Italy) LECT 5. NUTRITION IN PRETERM INFANTS: CERTAINTIES AND DOUBTS • L. Maggio (Rome, Italy) LECT 6. DONKEY MILK: A REVOLUTION IN HUMAN NUTRITION SINCE NEONATAL AGE • E. Bertino, G. Maiocco, C. Peila (Turin, Italy) LECT 7. OBESITY FROM THE FETUS TO THE ADULT: STATE OF THE ART • G.V. Dedoussis (Athens, Greec) LECT 8. NEONATAL ASPHYXIA: HYPOTHERMIA AND MELATONIN • E. Gitto, S. Manti, P. Romeo (Messina, Italy) LECT 9. RESPIRATORY SYNCITIAL VIRUS INFECTION: NOT ONLY PRETERM INFANTS • F. Gallini, F. Serrao, F. Cota, G. Vento (Rome, Italy) LECT 10. SEVERE BRONCHIOLITIS AS A CAUSE OF ARDS: PHYSIOPATOLOGY AND MANAGEMENT • C. Moretti (Rome, Italy) LECT 11. THE SOUND OF SILENCE IN THE NEONATAL INTENSIVE CARE UNIT: SPEECH AND MUSIC INSIDE AN INCUBATOR • A. Berger, L. Bartha-Doering, K. Klebermass-Schrehof, V. Giordano (Vienna, Austria) LECT 12. THE MICROBIOME IN PERINATAL MEDICINE: A PROTAGONIST • V. Fanos, R. Pintus (Cagliari, Italy) LECT 13. NEW AND OLD STRATEGIES TO PREVENT NEONATAL INFECTIONS • G. Corsello (Palermo, Italy) LECT 14. NECROTIZING ENTEROCOLITIS: LOOKING TO OLD DATA WITH NEW EYES • K.G. Sylvester (Palo Alto, USA) LECT 15. VACCINATION IN PRETERM AND LOW BIRTH WEIGHT INFANTS IN INDIA  • S. Soans, A. Mihalyi, V. Berlaimont, S. Kolhapure, R. Dash, A. Agrawal (Mangalore, Mumbai, Bengaluru and Hyderabad, India and Wavre, Belgium) LECT 16. PRESEPSIN: A NEW DIAGNOSTIC BIOMARKER IN EARLY-ONSET NEONATAL SEPSIS • E. D'Adamo, V. Botondi, D. Gazzolo (Chieti, Italy) LECT 17. CONTROVERSIES IN SCREENING AND PRENATAL DIAGNOSIS • G. Monni, A. Piras, R.M. Ibba, F. Dessolis (Cagliari, Italy) LECT 18. INDUCTION OF LABOUR: WHEN, HOW, WHY • S. Angioni, S. Pazzagli, M.N. D'Alterio, S. Sanna, E. Proto (Cagliari, Italy) LECT 19. PREECLAMPSIA, FETAL INTRAUTERINE GROWTH RESTRICTION AND MATERNAL CARDIOVASCULAR ADAPTATION: A KEY TO FIND A NEW THERAPEUTICAL APPROACH • H. Valensise, D. Farsetti, F. Pometti, B. Vasapollo, G.P. Novelli (Rome, Italy) LECT 20. HOW TO FEED AN IUGR NEWBORN: A NEW CHALLENGE FOR THE NEONATOLOGIST • A. Reali, G. Concas, G. Serrau, E. Coni (Cagliari, Italy) LECT 21. VITAMIN D FROM THE ANCIENT WORLD TO THE FUTURE • C. Romagnoli (Rome, Italy) LECT 22. HIGHLIGHTS FROM THE NATIONAL CONGRESS OF THE ITALIAN SOCIETY OF CHILDHOOD AND ADOLESCENT GYNECOLOGY • A.M. Fulghesu, S. Di Michele, E. Pittui (Cagliari, Italy) LECT 23. LONG-TERM OUTCOME OF INFANTS WITH INTRAUTERINE GROWTH RESTRICTION • P. Schiavolin, M. Fumagalli, F. Mosca (Milan, Italy) LECT 24. PRECISION MEDICINE IN PEDIATRIC IMMUNO-ALLERGOLOGY: THE ASTHMA MODEL • R. Castagnoli, A. Licari, G.L. Marseglia (Pavia, Italy) LECT 25. A MODERN CONCEPT OF THERMALISM APPLIED TO HEALTH AND WELL-BEING. A SYSTEMS MEDICINE MODEL OF INTEGRATION IN CLINICAL PRACTICE AND NEW THERAPEUTIC SOLUTIONS • U. Solimene (Milan, Italy) LECT 26. RARE DISEASES: FROM GENOMICS TO ESONOMICS • C. Salpietro (Messina, Italy) LECT 27. "THE HOUSE WITH THE WINGS" • G. Perricone (Palermo, Italy) LECT 28. THE BURDEN OF COVID-19 IN CHILDREN AND ADOLESCENTS • D.A. Pleșca, A.C. Drăgnescu, C. Rădulescu, A. Vilaia, V.Ș. Pleșca (Bucharest, Romania) LECT 29. THE NATURAL HISTORY OF POMPE DISEASE • S. Savasta (Cagliari, Italy) LECT 30. THE NETWORK OF THE ITALIAN ASSOCIATION OF PEDIATRIC HEMATOLOGY AND ONCOLOGY (AIEOP) CENTERS AS A MODEL OF NATIONAL AND INTERNATIONAL COOPERATION • F. Fagioli (Turin, Italy) LECT 31. BREASTFEEDING AND NUTRITION IN POST COVID-19: EXPERIENCE AND WISDOM • A. Dessì, A. Bosco (Cagliari, Italy) LECT 32. COMPLEMENTARY FEEDING: METABOLOMICS DATA • A. Bosco (Cagliari, Italy) LECT 33. AUTISM SPECTRUM DISORDER (ASD): COMBINING CLINICAL AND RESEARCH APPROACHES • M. Siracusano, A. Riccioni, L. Arturi, L. Mazzone (Rome, Italy) LECT 34. HOW GUT MICROBIOTA IMPACTS AUTISM SPECTRUM DISORDER • M. Mussap (Cagliari, Italy) LECT 35. THE MYSTERIES OF SLEEP IN PEDIATRIC AGE • M. Carotenuto (Naples, Italy) LECT 36. PERIODIC FEVER, APHTHOUS STOMATITIS, PHARYNGITIS, ADENITIS (PFAPA): A MISTERY TO RESOLVE • S. Leonardi (Catania, Italy) LECT 37. OUR CHILDREN ON OUR PLANET: INTRODUCTION TO THE TOPIC • V. Fanos, R. Pintus (Cagliari, Italy) LECT 38. THERAPEUTIC CHOICES AND RESPECT FOR THE ENVIRONMENT • S. Bernasconi (Parma, Italy) LECT 39. ENVIRONMENTAL ENDOCRINE DISRUPTORS AND THE MOTHER-INFANT DYAD: THE LIFE MILCH PROJECT • P. Palanza (Parma, Italy) LECT 40. QUANTITATIVE ANALYSIS OF PHTHALATES, BISPHENOLS, PARABENS, PYRETHROIDS, PAHs, POLAR PESTICIDES AND METALS IN BABY BOTTLES AND INFANT FORMULA, TO DEFINE THEIR ROLE AS EDCs IN THE LIFE MILCH PROJECT • A.M. Papini (Florence, Italy) LECT 41. ENDOCRINE DISRUPTORS: EFFECTS AND CONSEQUENCES • M.E. Street (Parma, Italy) LECT 42. OXYSTEROLS, OXIDATION AND MILK QUALITY: A NEW PARAMETER • F. Canzoneri, M. Charron, R. Menta (Alba, Italy) LECT 43. EVOLUTION OF THE INTESTINAL MICROBIOTA: EACH AGE HAS ITS OWN SPECIFICITIES • G. Bona (Novara, Italy) LECT 44. REGRESSION ALGORITHMS & PATTERN RECOGNITION FOR AUGMENTED EPIDEMIOLOGY • A. Colangelo (Trento, Italy)